Magnitude and determinants of alcohol use disorder among adult population in East Asian countries: A systematic review and meta-analysis - Belay, Getaneh Mulualem; Lam, Katherine Ka Wai; Liu, Qi; Wu, Cynthia Sau Ting; Mak, Yim Wah; Ho, Ka Yan (Frontiers in Public Health, 2023)
Introduction: Alcohol use disorder is a medical condition characterized by an impaired ability to control or stop alcohol use despite adverse health outcomes. Despite several studies that have analyzed the prevalence and determinants, their results have been equivocal, and the reasons for the differences in prevalence rates and determinants of AUD across nationalities are unknown. Hence, this study estimated the pooled prevalence of alcohol use disorder and its determinant among adults in East Asian countries. Methods: Articles were searched from PubMed, Web of Science, EMBASE, PsycINFO, and Scopus. All observational study designs that fulfilled the predefined criteria were included in the study. The findings were reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). The quality and heterogeneity of articles were assessed using the new castle-Ottawa scale (NOS) and I2, respectively. Additionally, publication bias was checked through funnel plot and Egger’s regression test. Results: A total of 14 articles with 93, 161 study participants were considered in the study. Of which 9 studies were included in the meta-analysis of the one-year prevalence of alcohol use disorder, 6 in the lifetime, 9 in alcohol abuse, and 8 in alcohol dependency. Consequently, the overall pooled prevalence of one-year alcohol use disorder was 8.88% (95% CI: 6.32,11.44), lifetime 13.41% (95%CI: 8.48, 18.34), alcohol abuse 5.4% (95% CI: 2.66,8.13), and alcohol dependency 4.47% (95% CI: 2.66, 6.27). In the subgroup analysis by country, the highest one-year and lifetime pooled prevalence of alcohol use disorder was observed in Korea at 9.78% (95% CI:4.40,15.15) and 16.73% (95% CI: 15.31, 18.16), respectively. Besides, smoking (OR: 3.99; 95% CI: 1.65,6.33) and male gender (OR: 5.9; 95% CI: 3.3,8.51) were significant determinants of alcohol use disorder. Conclusions: The magnitude of alcohol use disorder was high among adults in East Asian countries. Smoking and male gender were the key determinants of alcohol use disorders.